The Effect of Cognitive Style and Learning Interest on Understanding Physics Concepts - Samsun, Samsun; Tjalla, Awaludin; Sarifah, Iva (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to test the truth of the hypothesis and analyze the Influence of Perception of Cognitive Style and Learning Interest on Understanding Physics Concepts. The study used a survey method. The population of the study were students in four study programs at the Health Polytechnic in South Jakarta with a sample size of 88 people. The sampling technique used random sampling. The study used a questionnaire on perception of cognitive style, a questionnaire on learning interest and a test of understanding physics concepts. The data analysis used multiple linear regression. The conclusions obtained from the hypothesis testing are: 1) There is a significant influence of perception of cognitive style and learning interest together on students' understanding of physics concepts. This is evidenced by the sig value of 0.000 <0.05 and Fcount = 26.084. 2) There is a significant influence of perception of cognitive style on students' understanding of physics concepts. This is evidenced by the sig value of 0.047 <0.05 and tcount = 2.013. 3) There is a significant influence of learning interest on students' understanding of physics concepts. This is proven by the acquisition of sig value 0.001 < 0.05 and tcount = 3.426.